Single-Incision Laparoscopic Splenectomy and Splenic Autotransplantation for an Enlarged Wandering Spleen with Torsion - Katsura, Shunsaku (European J Pediatr Surg Rep, 2013)
A wandering spleen is a rare condition in which the spleen is not located in the left upper quadrant, but instead is found in the lower abdomen or in the pelvic region because of the laxity of the peritoneal attachments. The unusually long pedicle is susceptible to twisting, which can lead to ischemia, and eventually to necrosis. We herein report a case of an enlarged wandering spleen with torsion, successfully treated by single-incision laparoscopic splenectomy and autotransplantation. The transplanted splenic tissues could be identified on a spleen scintigram obtained 3 months after the surgery. Howell-Jolly bodies were not observed in blood specimens. This procedure is able to prevent an overwhelming postsplenectomy infection, and leads to satisfactory cosmetic results.